Northern Shrimp (Pandalus borealis) on Flemish Cap Surveys 2006 - Casas-Sánchez, José Miguel (2006)
A stratified random bottom trawl survey on Flemish Cap was carried out from June 28th to July 27th 2006. The area surveyed was extended up to depths of 800 fathoms (1400 meters) following the same procedures as in previous years and increasing the number of hauls planned (195). A total of 179 valid hauls were made by the vessel R/V Vizconde de Eza with the usual survey gear (Lofoten), 115 up to 730 meters depth. The general indexes for shrimp were estimated taken into account the traditional swept area (strata 1-19, up to depths of 730m.) and the total area surveyed (strata 1-34, up to depths of 1400m). The results concerning shrimp are presented and compared to those from previous years of the same series. The biomass and abundance have dropped significantly in 2006 at levels prior to 1998. Although this fall was produced in all age classes with the exception of age 4, the decreasing was mainly due to reduction of 3 year olds individuals (about 67% in number respect the last year). The decreasing of female biomass was less remarkable mostly due to the less importance of the 3 age-class in this sex group and the increasing of the 4 age-class respect of 2005 as a result of the 2002 strong year-class. Also, as in the last years (2004 and 2005) the youngest specimens (age 1) didn't appear in the catches, and they were weakly presents in the small mesh size bag attached to the cod-end, suggesting the absence of any strong year-classes since 2003.